Between two Opposite Nationalisms: The Friulan Community of Gorizia - Sartori, Chiara (Richtmann Publishing, 2012)
This paper is an excerpt from my Ph.D. dissertation. In my thesis I investigated Nationalism and Localism in Goriziathrough history and politics. In this brief version of the paper I present some of the results of my inquiry on Friulan community ofGorizia. After a short description of Friulan culture and language, I will discuss the role of Friulan culture in Gorizia in mediatingbetween national feelings and sense of local belonging. Gorizia is a city located on the border between Italy and Slovenia.Friulans, Italians, Slovenians and Germans cohabitated peacefully in the city until the rise of Nationalisms and the cruelty ofTotalitarianisms led to the building of the modern borders and to the separation of the groups. Friulans are catholic as theSlovenes and latin speakers as the Italians. As for the Slovene minority, they struggled to defende their culture and languagefrom Italianisation. On the same time, the protagonists of Gorizian Italian Irredentism were also Friulans, and many Friulans areproud to be Italian. Through the example of some semi structured interviews I carried on in Spring 2007, I will picture the Friulanfringe of Gorizia in the nowadays.